(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Learning to read is not merely a classroom requirement; it is a skill that empowers individuals, enabling them to navigate the complexities of the world and fostering a lifelong love for learning. The objectives of this research are formulated to investigate the English teacher of perception about cooperative learning. The study employed a case study research approach. A case study is a method used to gain a comprehensive comprehension of a subject or event in an authentic environment. The result study shows that The effectiveness of a teaching method is contingent upon various factors, including the specific context, learning objectives, and the preferences of both teachers and students. While cooperative learning has demonstrated efficacy in numerous scenarios, it is recognized that alternative methods may also be suitable depending on the unique needs and characteristics of the class. This highlights the value of educators being open to exploring and adapting different instructional strategies to best meet the requirements of their students.